Pengaruh Literasi Keuangan, Pendapatan dan Technology Acceptance Model (Tam) terhadap Minat Penggunaan Quick Response Indonesian Standar (QRIS) pada Pelaku UMKM di Kecamatan Temanggung - Rangga Bayu Kresna; Nugroho SBM (Universitas Diponegoro, 2022)
QRIS is a payment instrument officially issued by Bank Indonesia to be used in daily payment transaction activities by the public. MSMEs are an important sector in the use of QRIS as a transaction tool. However, MSMEs in Temanggung District have not fully used QRIS as part of their payment transaction activities. There are many factors that cause these problems to occur including financial literacy, income, and the basic concepts of the Technology Acceptance Model (TAM), namely perceptions of usefulness and perceptions of ease in applying interest in using QRIS. This study aims to analyze the effect of variables related to these problems, namely financial literacy, income, perceived usefulness, and perceived ease of use on interest in using QRIS for SMEs in Temanggung District. This research uses multiple regression analysis methods in empirical testing. The data used are primary data obtained from distributing questionnaires using a Likert scale, with the subject of active MSMEs in Temanggung District. This study uses the SPSS 26.0 application as an analytical tool. From the results of the analysis carried out, this study shows that the financial literacy variable has a significant influence on the interest in using QRIS. The income variable has no significant effect on interest in use. Variables of perceived usefulness and perceived ease of use also have no significant effect. The variables of financial literacy, income, perceived usefulness, and perceived ease of use simultaneously have a positive and significant effect. Of these variables, financial literacy has the greatest influence on interest in using QRIS. Therefore, the government needs to pay attention to and strengthen policies, especially in the field of financial literacy as the main factor in increasing the interest of MSMEs and the public in using QRIS as a means of payment transactions.